Greek papyri in the British museum ... - Kenyon, Frederic G.; Bell, Harold Idris; Crum, Walter Ewing (British museum, 1893)
Catalogue, with texts: [vol. I] ed. by F. G. Kenyon [Papyri acquired to end of 1890] 1893.--[vol.] II ed. by F. G. Kenyon [Papyri acquired 1890-95] 1898.--[vol.] III ed. by F. G. Kenyon and H. I. Bell [Papyri acquired 1895-1903] 1907.--[vol.] IV. The Aphrodito papyri, ed. by H. I. Bell ... with an appendix of Coptic papyri, ed. by W. E. Crum. 1910.--[vol.] V ed. by H. I. Bell [Byzantine papyri: Aphrodito, Syene, etc.] 1917.- VII. The Zenon archive, ed. by T.C. Skeat. 1974.